The Incredible Woman: Power and Sexual Politics by Jocelynne A Scutt - Petersson, Sandra (Victoria University of Wellington Law Review, 2000)
This article is a book review of Jocelynne A Scutt The Incredible Woman: Power and Sexual Politics (Artemis Publishing, Melbourne, 1997) (vol 1, 336 + xiv pages, $AUS34.95; vol 2, 354 + xvii pages, $AUS34.95). The book is an anthology of scholarship that acts as a catalogue of the wrong standards that the law has applied to women's performances and women's experiences. Petersson stresses the importance of this book for feminist legal scholarship as it increases the volume of such works, increasing the possibility of political change. Scutt's book is praised for being an exemplary voice for raising awareness in this area by making the message clear and accessible.